2013
DOI: 10.1016/j.humpath.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal γδ T-cell lymphomas are most frequently of type II enteropathy-associated T-cell type

Abstract: Summary Enteropathy-associated T-cell lymphoma includes type I cases and distinctive type II cases that, according to 2008 and 2010 World Health Organization descriptions, are T-cell receptor β+. Although T-cell receptor γδ enteropathy-associated T-cell lymphomas are reported, it is unknown if they have distinctive features and if they should be categorized as enteropathy-associated T-cell lymphoma or as a mucocutaneous γδ T-cell lymphoma. To address these questions, the clinicopathologic, immunophenotypic, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Loss of CD5 expression has been considered an aberrant immunophenotypic feature, useful for identifying the neoplastic Tc, in the PB and in the involved tissues [191]. However, this characteristic may only traduce a terminal differentiation of the neoplastic Tc into CTL, as occurs in γδ Tc LGL leukemia [23], cutaneous γδ Tc lymphoma [192] and intestinal γδ Tc lymphoma [193]; or a premature loss of CD5 expression in activated, functionally-immature, cytotoxic, neoplastic Tc, as happens in hepatosplenic γδ Tc lymphoma [48].…”
Section: Cd5 Signaling Moleculementioning
confidence: 99%
“…Loss of CD5 expression has been considered an aberrant immunophenotypic feature, useful for identifying the neoplastic Tc, in the PB and in the involved tissues [191]. However, this characteristic may only traduce a terminal differentiation of the neoplastic Tc into CTL, as occurs in γδ Tc LGL leukemia [23], cutaneous γδ Tc lymphoma [192] and intestinal γδ Tc lymphoma [193]; or a premature loss of CD5 expression in activated, functionally-immature, cytotoxic, neoplastic Tc, as happens in hepatosplenic γδ Tc lymphoma [48].…”
Section: Cd5 Signaling Moleculementioning
confidence: 99%
“…Cytogenetic studies have demonstrated gains and translocations of MYC (8q24) 10 , 13 , 16 in EITL, although they may also be seen in classical EATL. 17 Conversely, gains of 1q32.2-q41 and 5q34-q35.2 are more common in EATL compared with EITL, whereas 9q31.3 gain and 16q21.1 loss can be observed in both classical EATL and EITL. 1 , 3 Recently, it was reported that an activating STAT5B p.N642H mutation is common in T-cell lymphoma derived from γδ T-cells, including some cases of EITL.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the expression of the TCR is an indicator, though no discriminator, differentiating between MEITL and EATL with statistical significance. 37 In addition, our study adds to the notion that the loss of TCR expression is common in EATL. 34,38 As a main finding in our study, SYK is strongly expressed in the vast majority of MEITL cases.…”
Section: Discussionmentioning
confidence: 68%